Electrochemical corrosion-resistant and degradation-resistant material as well as construction method and application thereof
Through the composite coating of biological functional fillers and hydrogel polymer materials, combined with circulating freezing-thawing and salting out treatment, the problems of insufficient corrosion and biocompatibility of magnesium alloys are solved, and the high cellular activity of magnesium alloy materials is achieved. Antibacterial and structural strength, suitable for medical implant interventional devices.
Patent Information
- Application Number
- CN202411380753.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The rapid corrosion of magnesium alloys in the physiological environment leads to hydrogen release, triggering gas cavity and local alkalization reactions, reducing mechanical strength, and the toughness of existing biocompatible polymer materials is insufficient, making it difficult to promote cell adhesion and tissue repair. The adhesion between the coating and the substrate is insufficient.
Using a composite coating of biological functional fillers and hydrogel polymer materials, the structural strength and adhesion of the coating are enhanced through cyclic freezing-thawing and salting treatment, and a bioactive toughening coating is formed on the surface of magnesium alloy to regulate Electrochemical degradation of materials.
The high cellular activity, antibacteriality and structural strength of the material under an environment of 37°C are achieved, and the degradation weight loss is less than 6 wt%, which is suitable as a biological functional implant material for medical implant interventional devices.
Smart Images

Figure CN119280481A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of surface treatment and coating of medical materials, and in particular to an electrochemical corrosion and degradation resistant material and a construction method and application thereof. Background Art
[0002] Magnesium alloy, as a new type of medical metal material, has received extensive attention in the biomedical field due to its excellent mechanical properties, good biocompatibility and degradability. Nevertheless, the rapid corrosion behavior of magnesium alloys in physiological environments may lead to a series of problems. Specifically, the corrosion of magnesium alloys will produce hydrogen (H2), which may lead to subcutaneous gas accumulation and the formation of gas cavities, which in turn will cause separation of the tissue-implant interface and increase the risk of surgical failure. In addition, when the pH value of the local microenvironment rises to above 7.8, the local alkalinization reaction caused by hydrogen release may induce tissue alkalosis. At the same time, the precipitation and alkalinization reaction of hydrogen will accelerate the decrease in the mechanical strength of magnesium alloy materials, which may lead to premature failure of implants. Therefore, improving the corrosion resistance of magnesium alloys is crucial for their application in implantable medical devices.
[0003] In the prior art, the method of preparing a protective coating on the surface of magnesium alloy has been proven to effectively slow down the corrosion rate of magnesium alloy and control its corrosion behavior. Polymer hydrogel, as a material with good biocompatibility, shows broad application prospects in the field of tissue repair due to its excellent corrosion resistance and adjustable structural functions. However, due to the limitations of molecular structure, existing biocompatible polymer materials usually have low toughness and insufficient biological activity, making it difficult to effectively promote cell adhesion and tissue repair. In addition, hydrogels have fewer surface active groups and are difficult to form a stable covalent bond structure with the surface of magnesium alloy, resulting in insufficient adhesion between the coating and the substrate, thereby affecting the stability and effectiveness of the coating.
[0004] At present, CN 117531045 A uses plasma-treated magnesium alloy as a substrate and obtains a composite coating through dopamine self-polymerization reaction. The coating can not only delay the degradation rate of the magnesium alloy substrate and have a biologically active load function, but also the composite coating can be continuously degraded in the body and has good biocompatibility. CN 114601962 A is based on a self-polymerized dopamine coating, and a graphene ultra-thin coating is attached to the surface of the dopamine coating through the principle of physical and chemical vapor deposition, which effectively inhibits the electrochemical reaction of magnesium alloy degradation. The preparation efficiency of this method is not high, and the chemical deposition is slow. Although the graphene coating has a good electrochemical inhibition effect, its biological activity in the body is still questionable.
[0005] At the same time, CN 116479500 A uses the principle of electrophoretic deposition to place the magnesium alloy in a polytetrafluoroethylene solution dissolved in ethanol, performs physical deposition at a voltage of 30-100V, and then performs drying and sintering to improve the corrosion resistance of the magnesium alloy. The coating prepared by this method is a pure polytetrafluoroethylene material, which has good biocompatibility but insufficient biological activity; and polytetrafluoroethylene has fewer surface active groups, and the interface performance combining with the magnesium alloy needs to be improved. Summary of the invention
[0006] The purpose of the present invention is to provide an electrochemical corrosion-resistant and degradation-resistant material, which has a functional composite coating, unique biological activity, antibacterial properties, structural strength and toughness, and controllable material degradation, and is particularly suitable for use as a biological functional implant material in medical implant interventional devices.
[0007] According to the first aspect of the present invention, the present invention provides an electrochemical corrosion resistant and degradation resistant material, the surface of the material includes a composite coating, the composite coating contains a biofunctional filler and a hydrogel polymer material; the composite coating has a corrosion voltage of not less than -1.05V under a 37°C environment, a cell activity of more than 1.2OD / 450nm after 14 days of use, and a peel strength of not less than 300J / m 2 The adhesion level is above level 3, and the degradation weight loss in 28 days is not higher than 6wt%.
[0008] According to a second aspect of the present invention, the present invention provides a method for constructing the electrochemical corrosion resistant and degradation resistant material of the present invention, the method comprising: (1) forming a precursor solution of a biofunctional filler-hydrogel composite coating; (2) immersing a substrate in the precursor solution, pulling, cyclically freezing-thawing, and salting out; wherein the immersion solution used for salting out is selected from sodium salt and / or potassium salt.
[0009] According to a third aspect of the present invention, the present invention provides a use of the electrochemical corrosion and degradation resistant material of the present invention in a medical implant repair device.
[0010] The electrochemical corrosion-resistant and degradation-resistant material of the present invention has a functional composite coating, and possesses unique biological activity, antibacterial properties, structural strength and toughness, and controllable material degradation, and is particularly suitable for use as a biological functional implant material in medical implant interventional devices.
[0011] The electrochemical corrosion and degradation resistant material and its construction method provided by the present invention, the bioactive functional filler is compounded with the hydrogel to form an active coating; and the coating structure strength is further improved by the coating salting-out toughening and strengthening treatment technology; and then the coating adheres to the rough surface of the substrate to form a bioactive toughened coating, thereby improving the biological activity of the material and regulating the electrochemical degradation of the material through the coating to provide long-term stable structural support. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a real picture of the example and comparative example materials 1 hour after preparation, which shows that the toughening method provided by the present invention can effectively improve the structural stability of the coating. In comparison, the coating of the control group without toughening treatment is prone to fall off.
[0013] Figure 2 This is a comparison of the morphologies of the example and comparative example materials after 28 days of degradation after preparation, indicating that the corrosion resistance of the magnesium alloy material is significantly improved after composite coating coating and toughening and strengthening treatment. Compared with the control group, the experimental group is still structurally stable after 28 days of corrosion immersion. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] The present invention provides an electrochemical corrosion resistant and degradation resistant material. The surface of the material comprises a composite coating, and the composite coating comprises a biofunctional filler and a hydrogel polymer material. The composite coating has a corrosion voltage of not less than -1.05V under a 37°C environment, a cell activity of more than 1.2OD / 450nm after 14 days of use, and a peel strength of not less than 300J / m 2 The adhesion level is above level 3, and the degradation weight loss in 28 days is not higher than 6wt%.
[0016] The electrochemical corrosion-resistant and degradation-resistant material of the present invention has a functional composite coating, and possesses unique biological induction activity, antibacterial properties, structural strength and toughness, and controllable material degradation, and is particularly suitable for use as a biological functional implant material in medical implant interventional devices.
[0017] According to a preferred embodiment of the present invention, the composite coating of the present invention has a corrosion voltage of -1.05V to -0.8V at 37°C, a cell activity range of 1.2 to 1.6 OD / 450nm after 14 days of use, and a peel strength of 300 to 600 J / m 2 The adhesion level is 3 to 5, and the degradation weight loss after 28 days is 3 to 6 wt%.
[0018] In the present invention, the optional range of the hydrogel polymer material is relatively wide, and the following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the hydrogel polymer material is selected from one or more of polyvinyl alcohol, chitosan, hyaluronic acid, sodium alginate, silk fibroin, collagen, and gelatin.
[0019] In the present invention, there is no special requirement for the type of substrate of the electrochemical corrosion resistant and degradation resistant material of the present invention. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the substrate can be selected from one or more of alloy materials, ceramic materials, and bioactive glass, preferably alloy materials, and more preferably magnesium alloy materials. The present invention has no special requirements for the shape of the substrate, which can be a flat plate or an irregular curved surface. In the embodiments of the present invention, the substrate is a magnesium alloy to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.
[0020] According to a preferred embodiment of the present invention, the biological functional filler comprises a biological filler and a functional drug, and the functional drug is selected from growth factors and antibacterial agents.
[0021] In the present invention, there is no special limitation on the content of functional drugs in the biofunctional filler. According to a preferred embodiment of the present invention, the content of the functional drugs is 1-5wt% based on the total weight of the biofunctional filler. The material of the present invention that meets the above characteristics has good bio-induction activity.
[0022] In the present invention, there is no special limitation on the content relationship between the growth factor and the antibacterial agent in the functional medicine. According to a preferred embodiment of the present invention, the mass ratio of the growth factor to the antibacterial agent is 1:0.1-10, preferably 1:0.2-5. The material of the present invention that meets the above characteristics has good biological induction activity and antibacterial properties.
[0023] In the present invention, the content of the biofunctional filler can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the content of the biofunctional filler is 1-30wt%, preferably 5-20wt%, based on the total weight of the composite coating.
[0024] In the present invention, the types of the biological fillers can be selected from a wide range, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the biological filler is selected from inorganic bioactive materials for bone repair, preferably selected from one or more of silicate bioglass, phosphate bioglass, borate bioglass, and hydroxyapatite.
[0025] In the present invention, the types of growth factors can be selected from a wide range, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the growth factor is selected from one or more of IGF-like insulin growth factor, BMP bone morphogenetic protein, and transforming growth factor-β.
[0026] In the present invention, there is no special requirement for the type of the antibacterial agent, and conventional antibacterial agents in the art can meet the requirements of the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the antibacterial agent is selected from broad-spectrum antibiotics and / or non-antibiotic antibacterial agents.
[0027] In the present invention, the types of the broad-spectrum antibiotics can be selected from a wide range, which are exemplified below but are not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the broad-spectrum antibiotics are selected from one or more of vancomycin, gentamicin, cephalosporin, amoxicillin and tobramycin.
[0028] In the present invention, there is no special requirement for the type of the non-antibiotic antibacterial agent, for example, chlorhexidine.
[0029] In the present invention, there is no specific requirement for the form of the biofunctional filler, which may be in the form of particles or fibers.
[0030] In the present invention, the particle diameter of the particle form can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the particle diameter of the particle form is 0.5-200 μm, preferably 10-100 μm. The material of the present invention that meets the above characteristics has better structural strength and toughness.
[0031] In the present invention, the fiber morphology is short fiber morphology, and the distribution form is random distribution. There is no special requirement for the length and diameter of the fiber. According to a preferred embodiment of the present invention, the length of the fiber is 0.1-5 mm, preferably 0.5-3 mm; the diameter of the fiber is 1-20 μm, preferably 3-10 μm. The material of the present invention that meets the above characteristics has better structural strength and toughness.
[0032] The present invention provides a method for constructing the electrochemical corrosion and degradation resistant material of the present invention, the method comprising: (1) forming a precursor solution of a biofunctional filler-hydrogel composite coating; (2) immersing a substrate in the precursor solution, pulling, cyclically freezing-thawing, and salting out; wherein the immersion solution used for salting out is selected from an aqueous solution of sodium salt and / or potassium salt.
[0033] The present invention adopts salting-out treatment, through immersion, so that the composite coating undergoes physical and chemical reactions such as dehydration, hydrogen bond crosslinking, ion crosslinking, etc. in the salt solution, thereby making the hydrogel molecular chain structure in the composite coating more dense, achieving a significant improvement in the strength and toughness of the coating structure, i.e., a toughening effect.
[0034] According to a preferred embodiment of the present invention, in step (2), during the freezing-thawing cycle, the freezing temperature is -25 to -15°C; and / or the freezing time is 6 to 24 hours. The above technical solution can avoid the use of hydrogel crosslinking agents, retain the best hydrogel biocompatibility, and has a biosafety advantage.
[0035] According to a preferred embodiment of the present invention, in step (2), in the freeze-thaw cycle, the thawing time is 2-6°C; and / or the thawing time is 6-24h. The above technical solution can avoid the use of hydrogel crosslinking agents, retain the best hydrogel biocompatibility, and has a biosafety advantage.
[0036] According to a preferred embodiment of the present invention, in step (2), the number of cycles in the cyclic freezing-thawing is 1-6 times, preferably 2-4 times. The above technical solution can avoid the use of hydrogel crosslinking agents, retain the best hydrogel biocompatibility, and has a biosafety advantage.
[0037] In the present invention, in step (2), the type of the impregnation solution can be selected from a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the impregnation solution is selected from one or more aqueous solutions of sodium citrate, sodium chloride, sodium sulfate, sodium phosphate, potassium chloride, potassium sulfate, and potassium phosphate.
[0038] According to a preferred embodiment of the present invention, the impregnation solution is a mixed aqueous solution of sodium salt and potassium salt, preferably a mixed aqueous solution of sodium citrate and potassium chloride, and the content of sodium citrate and potassium chloride is not less than 40% respectively based on the total molar content of salt in the impregnation solution. The above technical solution can further enhance the structural performance advantages of the composite coating.
[0039] In the present invention, in step (2), the concentration of the impregnation solution can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the concentration of the impregnation solution is 0.1-3 mol / L, preferably 1-2 mol / L.
[0040] In the present invention, there is no special requirement for the immersion time in the salting-out treatment. The following is an exemplary description, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the immersion time is 10-90 min, preferably 20-40 min.
[0041] In the present invention, in step (2), the pulling interval time can be determined according to specific working conditions, for example, it can be 10-60 minutes, preferably 20-30 minutes.
[0042] In the present invention, in step (2), the number of times of pulling can be determined according to specific working conditions, for example, it can be 1-10 times, preferably 3-5 times.
[0043] In the present invention, in step (1), the method for forming a precursor solution of a biofunctional filler-hydrogel composite coating comprises: preparing a biofunctional filler, and mixing the biofunctional filler with a hydrogel precursor solution.
[0044] According to a preferred embodiment of the present invention, in the precursor solution of the biofunctional filler-hydrogel composite coating, the content of the biofunctional filler is 1-30wt%, preferably 5-20wt%.
[0045] In the present invention, there is no special requirement for the formation of the hydrogel precursor solution. For example, the hydrogel polymer material can be mixed with deionized water to obtain a mixed hydrogel precursor solution. The mixing conditions can be: a temperature of 40-95°C, preferably 60-90°C, a stirring speed of 100-400rpm, preferably 150-300rpm, and a time of 30-120min, preferably 60-90min. In the hydrogel precursor solution, the mass concentration of the hydrogel polymer material is between 5-40%, preferably 10-30%.
[0046] In the present invention, there is no specific requirement for the preparation of the biological functional filler. For example, the functional drug can be mixed with a solvent to obtain a dispersion, which can be sprayed on the surface of the biological filler and dried to obtain the biological functional filler.
[0047] In the present invention, there is no special requirement for the relative relationship between the contents of the functional drug and the solvent. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the mass ratio of the functional drug to the solvent is 1:200-2000, preferably 1:500-1500.
[0048] In the present invention, the types of the solvent can be selected from a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the solvent is selected from one or more of deionized water, acetic acid, butyl acetate, and acetone.
[0049] In the present invention, the purpose of drying is to volatilize the solvent. There is no specific requirement for the drying temperature. For example, the drying temperature can be 40-70° C., preferably 50-60° C.; the drying time can be 0.2-2 h, preferably 0.5-1 h.
[0050] In the present invention, the step of mixing the biofunctional filler with the hydrogel precursor solution includes: mixing the hydrogel matrix and the biofiller loaded with functional drugs, and then shearing, ultrasonication, and degassing. The shearing, ultrasonication, and degassing specifically include: using a high-speed shearing machine for high-speed shearing dispersion, the shearing time is 1-10min, preferably 3-7min, to form a mixed solution; then ultrasonic dispersion homogenization treatment is performed for 5-20min, preferably 10-15min; and then placing it in a vacuum exhaust device for exhaust treatment for 10-30min, preferably 15-20min, and removing bubbles in the mixed solution by negative pressure vacuum, and finally forming a biofunctional filler-hydrogel composite coating precursor solution. This is well known to those skilled in the art and will not be described in detail.
[0051] In the present invention, surface texturing of the substrate can improve the surface roughness of the substrate, achieve physical anchoring between the coating and the substrate, and improve the interface performance between the coating and the substrate. According to a preferred embodiment of the present invention, the surface texturing treatment includes: performing laser scanning on the surface of the substrate to form a texture.
[0052] In the present invention, there is no specific requirement for the type of texture, which can be a cross texture or a unidirectional texture, wherein the unidirectional texture angle can be selected between 0-360° to maintain unidirectional homogeneity; the cross texture can be formed by staggering 2 or more unidirectional textures, and the texture angle can be selected between 0-90°.
[0053] In the present invention, there is no special requirement for the parameters of the laser scanning conditions, as long as a rough and regularly evenly distributed texture can be formed on the surface of the substrate. The specific parameters depend on the actual working conditions. For example, if the substrate is made of magnesium alloy material, femtosecond or nanosecond laser can be used for scanning, preferably nanosecond laser. The laser power can be selected from 1-20kW / cm 2 , preferably 5-10kW / cm 2 , the scanning speed is 20-250 mm / s, preferably 50-150 mm / s, the scanning frequency is 10-40 kHz, preferably 20-35 kHz, and the scanning step length is 0.1-0.5 mm, preferably 0.2-0.4 mm.
[0054] The material obtained by the construction method provided by the present invention has unique biological induction activity, antibacterial property, structural strength and toughness, and controllable material degradation, and is particularly suitable for use as a biological functional implant material in medical implant interventional devices.
[0055] The present invention will be described in detail below by way of examples. In the following examples,
[0056] The corrosion voltage was measured by electrochemical test analysis in simulated body fluids;
[0057] On day 14, cell viability was measured by the CCK-8 method;
[0058] The coating peel strength was measured by the standard 90° peel test method (ISO 8510-1);
[0059] Adhesion grade The adhesion between the composite coating and the substrate surface is tested according to the ASTM-D-3359-2010 international standard. The results are divided into grades 0 to 5, where grade 0 is the worst adhesion and grade 5 is the best adhesion.
[0060] The 28-day degradation weight loss percentage was measured by the tape stripping test method;
[0061] Corrosion voltage (Ecoor / V), cell activity on day 14 (OD / 450nm), peel strength (J / m 2 ), adhesion level, and 28-day degradation weight loss (%) were all tested in vitro at 37°C.
[0062] The magnesium alloy is a commercial product with a grade of 99% medical high purity produced by Henan Mingmei Magnesium Technology Co., Ltd.
[0063] The silicate bioglass particles are homemade in the laboratory, with a diameter of 20 μm and a formula of 46 mol.% SiO2, 25 mol.% Na2O, 26 mol.% CaO, and 3 mol.% P2O5. ;
[0064] The silicate bioglass fiber was homemade in the laboratory, with a diameter of 7 μm and a formula of 46 mol.% SiO2, 25 mol.% Na2O, 26 mol.% CaO, and 3 mol.% P2O5.
[0065] The phosphate bioglass particles were homemade in the laboratory, with a diameter of 30 μm and a formula of 45 mol.% P2O5, 25 mol.% CaO, 20 mol.% MgO, and 10 mol.% Na2O.
[0066] The hydroxyapatite particles are commercially available products with the brand name H139936 produced by Aladdin.
[0067] IGF insulin-like growth factor is a commercial product produced by Aladdin with the brand name R283957.
[0068] Gentamycin is a commercial product produced by Aladdin Company with the brand name G302822.
[0069] Chitosan is a commercial product of Aladdin Company with brand number C105800.
[0070] Polyvinyl alcohol is a commercially available product with brand number 1548065 produced by Sigma-Aldrich.
[0071] Sodium chloride is a commercially available product with the brand name S9888 produced by Sigma-Aldrich.
[0072] Potassium chloride is a commercial product produced by Sigma-Aldrich with the brand name P3911.
[0073] Sodium citrate is a commercially available product with the brand name PHR1416 produced by Sigma-Aldrich.
[0074] In the following embodiments of the present invention, the magnesium alloy substrates used are subjected to surface polishing treatment before texturing treatment. There are no special requirements for the polishing treatment steps, and conventional polishing steps are applicable to the present invention, specifically comprising: polishing and grinding the surface of the magnesium alloy using metallographic sandpaper of P180, P220, P280, P360, P600, P1000, P1500, P2000, and P4000 in sequence, and then mechanically polishing the surface using polishing paste to finally form a glossy mirror surface, and then ultrasonically cleaning with ethanol and deionized water to remove surface impurities, and drying with compressed air to obtain a polished magnesium alloy substrate.
[0075] [Example 1]
[0076] a. Surface texturing treatment of magnesium alloy substrate
[0077] Nanosecond laser with a laser power of 5kW / cm 2 , scanning speed 70mm / s, scanning frequency 20kHz, scanning step length 0.2mm, texture texture is cross texture, texture angle 90°.
[0078] b. Preparation of biofunctional fillers
[0079] The biological filler uses silicate bioglass particles with a diameter of 20 μm, and the functional drugs loaded on the surface are IGF-like insulin growth factor and gentamicin, with a mass ratio of 1:1; then, using deionized water as the solvent, the drug and the solvent are mixed in a mass ratio of 1:1000 to obtain a dispersion, which is then sprayed on the filler surface and placed in a 50°C drying oven for 1 hour to evaporate all the solvents, and finally a drug-loaded coating is formed on the surface of the biological functional filler, and the functional drug accounts for 1% of the total mass of the biological functional filler.
[0080] c. Preparation of hydrogel precursor solution
[0081] The hydrogel matrix uses polyvinyl alcohol as a precursor, which is mixed with deionized water, stirred at a high temperature of 80° C. at a speed of 200 rpm for 60 minutes, and a hydrogel precursor solution is prepared at a mass concentration of 10%.
[0082] d. Composite coating preparation and toughening treatment
[0083] The biofunctional filler and the hydrogel precursor solution were mixed in a mass ratio of 1:5, dispersed by high-speed shear for 3 minutes to form a mixed solution, and then further ultrasonically dispersed for 10 minutes to obtain a homogenized mixed solution. The mixed solution was then vacuum-extracted for 15 minutes to remove bubbles in the mixed solution to form a biofunctional filler-hydrogel composite coating precursor solution.
[0084] The magnesium alloy flat plate with textured surface was immersed in the precursor solution and repeatedly pulled 3 times, each time with an interval of 20 minutes, so as to form a multi-layer composite coating precursor on the surface of the magnesium alloy, and then placed in a refrigerator according to the freeze-thaw method, frozen crosslinked in a 20°C environment for 6 hours, and then thawed in a 4°C environment for 6 hours, and this cycle was repeated 3 times to make the hydrogel completely physically crosslinked. Finally, it was placed in a sodium chloride solution (2mol / L) for toughening immersion salting-out treatment, and the treatment time was 20 minutes to form a magnesium alloy coated with a toughened structure composite hydrogel coating.
[0085] e. Material electrochemical degradation experiments, mechanical and biological tests
[0086] Through electrochemical test analysis in simulated body fluids, it can be seen that the corrosion voltage of magnesium alloy coated with composite coating is significantly improved to -8.13V;
[0087] The adhesion of the surface composite coating reaches the 5th level (from 1 to 5, the higher the level, the stronger the adhesion);
[0088] The peel strength of the composite coating reaches 500J / m2;
[0089] The biological activity of magnesium alloy materials was significantly improved. In the 14-day osteoblast culture, the cell activity optical value (OD / 450nm) was 1.1 on the 14th day.
[0090] The magnesium alloy plate was immersed in simulated body fluid for degradation, and the weight loss was 3.2% after 28 days of degradation. The specific data is shown in Table 1.
[0091] [Example 2]
[0092] a. Surface texturing treatment of magnesium alloy substrate
[0093] Same as Example 1.
[0094] b. Preparation of biofunctional fillers
[0095] The biological filler is silicate bioglass fiber with a length of 1 mm and a diameter of 7 μm. The functional drugs loaded on the surface are IGF insulin growth factor and gentamicin, with a mass ratio of 1:1; then, deionized water is used as the solvent, the drug and the solvent are mixed at a mass ratio of 1:1000 to obtain a dispersion, which is then sprayed on the filler surface and placed in a 50°C drying oven for 1 hour to evaporate all the solvents, and finally a drug-loaded coating is formed on the surface of the biological functional filler, and the functional drug accounts for 1% of the total mass of the biological functional filler.
[0096] c. Preparation of hydrogel precursor solution
[0097] Same as Example 1.
[0098] b. Composite coating preparation and toughening treatment
[0099] Same as Example 1.
[0100] e. Material electrochemical degradation experiments, mechanical and biological tests
[0101] See Table 1 for specific data.
[0102] [Example 3]
[0103] a. Surface texturing treatment of magnesium alloy substrate
[0104] Nanosecond laser with a laser power of 5kW / cm 2 , scanning speed 70mm / s, scanning frequency 20kHz, scanning step length 0.2mm, and texture is unidirectional texture.
[0105] b. Preparation of biofunctional fillers
[0106] Same as Example 1.
[0107] c. Preparation of hydrogel precursor solution
[0108] Same as Example 1.
[0109] d. Composite coating preparation and toughening treatment
[0110] Same as Example 1.
[0111] e. Material electrochemical degradation experiments, mechanical and biological tests
[0112] See Table 1 for specific data.
[0113] [Example 4]
[0114] a. Surface texturing treatment of magnesium alloy substrate
[0115] Same as Example 1.
[0116] b. Preparation of biofunctional fillers
[0117] The biological filler is phosphate bioglass particles with a diameter of 30 μm. The functional drugs loaded on the surface are IGF-like insulin growth factor and gentamicin, and the mass ratio of the two is 1:1; then, deionized water is used as the solvent, and the drug and the solvent are mixed in a mass ratio of 1:1000 to obtain a dispersion, which is then sprayed on the filler surface and placed in a 50°C drying oven for 1 hour to evaporate all the solvents, and finally a drug-loaded coating is formed on the surface of the biological functional filler. The functional drug accounts for 1% of the total mass of the biological functional filler.
[0118] c. Preparation of hydrogel precursor solution
[0119] Same as Example 1.
[0120] d. Composite coating preparation and toughening treatment
[0121] Same as Example 1.
[0122] e. Material electrochemical degradation experiments, mechanical and biological tests
[0123] See Table 1 for specific data.
[0124] [Example 5]
[0125] a. Surface texturing treatment of magnesium alloy substrate
[0126] Same as Example 1.
[0127] b. Preparation of biofunctional fillers
[0128] The biological filler is hydroxyapatite particles with a diameter of 5 μm, and the functional drugs loaded on the surface are IGF-like insulin growth factor and gentamicin, with a mass ratio of 1:1; then, using deionized water as the solvent, the drug and the solvent are mixed in a mass ratio of 1:1000 to obtain a dispersion, which is then sprayed on the filler surface and placed in a 50°C drying oven for 1 hour to evaporate all the solvents, ultimately forming a drug-loaded coating on the surface of the biological filler, and the functional drug accounts for 1% of the total mass of the biological functional filler.
[0129] c. Preparation of hydrogel precursor solution
[0130] Same as Example 1.
[0131] d. Composite coating preparation and toughening treatment
[0132] Same as Example 1.
[0133] e. Material electrochemical degradation experiments, mechanical and biological tests
[0134] See Table 1 for specific data.
[0135] [Example 6]
[0136] a. Surface texturing treatment of magnesium alloy substrate
[0137] Same as Example 1.
[0138] b. Preparation of biofunctional fillers
[0139] Same as Example 1.
[0140] c. Preparation of hydrogel precursor solution
[0141] The hydrogel matrix uses chitosan as a precursor, which is mixed with deionized water, stirred at 300 rpm for 90 minutes at a temperature of 70° C., and a hydrogel precursor solution is prepared at a mass concentration of 15%.
[0142] d. Composite coating preparation and toughening treatment
[0143] The biofunctional filler and the hydrogel precursor solution were mixed in a mass ratio of 1:5, dispersed by high-speed shear for 4 minutes to form a mixed solution, and then further ultrasonically dispersed for 15 minutes to obtain a homogenized mixed solution. The mixed solution was then vacuum-extracted for 10 minutes to remove bubbles in the mixed solution to form a biofunctional filler-hydrogel composite coating precursor solution.
[0144] The magnesium alloy flat plate with textured surface was immersed in the precursor solution and repeatedly pulled 5 times, each time with an interval of 15 minutes, so as to form a multi-layer composite coating precursor on the surface of the magnesium alloy, and then placed in a refrigerator according to the freeze-thaw method, frozen crosslinked in a 20°C environment for 12 hours, and then thawed in a 4°C environment for 12 hours, and this cycle was repeated 3 times to make the hydrogel completely physically crosslinked. Finally, it was placed in a sodium citrate solution (1.3 mol / L) for toughening immersion salting-out treatment, and the treatment time was 10 minutes to form a magnesium alloy coated with a toughened structure composite hydrogel coating.
[0145] e. Material electrochemical degradation experiments, mechanical and biological tests
[0146] See Table 1 for specific data.
[0147] [Example 7]
[0148] a. Magnesium alloy surface texturing
[0149] Same as Example 1.
[0150] b. Preparation of biofunctional fillers
[0151] Same as Example 1.
[0152] c. Preparation of hydrogel precursor solution
[0153] The hydrogel matrix uses polyvinyl alcohol and chitosan as precursors, which are configured in a 1:1 ratio, mixed with deionized water, stirred at 300 rpm for 90 min at 80° C., and a hydrogel precursor solution is prepared at a mass concentration of 15%.
[0154] d. Composite coating preparation and toughening treatment
[0155] According to the design requirements, the biofunctional filler and the hydrogel precursor liquid were mixed in a mass ratio of 1:5, dispersed by high-speed shear for 4 minutes to form a mixed liquid, and then further ultrasonically dispersed for 10 minutes to obtain a homogenized mixed liquid. The mixed liquid was then vacuum-exhausted for 15 minutes to remove bubbles in the mixed liquid to form a biofunctional filler-hydrogel composite coating precursor liquid.
[0156] The magnesium alloy flat plate with textured surface was immersed in the precursor solution and repeatedly pulled 5 times, each time with an interval of 20 minutes, so as to form a multi-layer composite coating precursor on the surface of the magnesium alloy, and then placed in a refrigerator according to the freeze-thaw method, frozen crosslinked in a 20°C environment for 12 hours, and then thawed in a 4°C environment for 12 hours, and this cycle was repeated 3 times to make the hydrogel completely physically crosslinked. Finally, it was placed in a sodium citrate solution (1.3 mol / L) for immersion salting out treatment, and the treatment time was 20 minutes to form a magnesium alloy coated with a toughened structure composite hydrogel coating.
[0157] e. Material electrochemical degradation experiments, mechanical and biological tests
[0158] See Table 1 for specific data.
[0159] [Example 8]
[0160] The method of Example 1 is followed, except that the magnesium alloy substrate is not subjected to surface texturing treatment. The performance test data is shown in Table 1.
[0161] [Example 9]
[0162] The method of Example 1 is different in that a mixed solution of sodium citrate and potassium chloride is used for toughening, impregnation and salting-out treatment in stage d, wherein the molar ratio of the content of sodium citrate and potassium chloride in the mixed solution is 1.5:1. The performance test data is shown in Table 1.
[0163] [Comparative Example 1]
[0164] The method of Example 1 was followed, except that an ethanol solution was used for impregnation in stage d. The performance test is shown in Table 1.
[0165] [Comparative Example 2]
[0166] The method of Example 1 is followed, except that no toughening treatment is performed in stage d. The performance test is shown in Table 1.
[0167] Table 1: Formulas and performance indicators of embodiments and comparative examples
[0168]
[0169] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrochemical corrosion and degradation resistant material, characterized in that: The surface of the material includes a composite coating, which contains a biofunctional filler and a hydrogel polymer material; The composite coating has a corrosion voltage of not less than -1.05V at 37°C, a cell activity of more than 1.2OD / 450nm after 14 days of use, and a peel strength of not less than 300J / m 2 The adhesion level is above level 3, and the degradation weight loss in 28 days is not higher than 6wt%.
2. The material according to claim 1, wherein The composite coating has a corrosion voltage of -1.05V to -0.8V at 37°C, a cell activity of 1.2 to 1.6 OD / 450nm after 14 days of use, and a peel strength of 300-600 J / m 2 , the adhesion level is 3 to 5, and the degradation weight loss after 28 days is 3 to 6 wt%; and / or The hydrogel polymer material is selected from one or more of polyvinyl alcohol, chitosan, hyaluronic acid, sodium alginate, silk fibroin, collagen, and gelatin; and / or The substrate of the electrochemical corrosion and degradation resistant material is one or more of an alloy material, a ceramic material, and a bioglass material, preferably an alloy material, and more preferably a magnesium alloy material; and / or The biological functional filler comprises a biological filler and a functional drug, wherein the functional drug is selected from growth factors and / or antibacterial agents; Preferably, the content of the functional drug is 1-5wt% based on the total weight of the biological functional filler; Preferably, in the functional drug, the mass ratio of the growth factor to the antibacterial agent is 1:0.1-10, preferably 1:0.2-5; and / or Based on the total weight of the composite coating, the content of the biofunctional filler is 1-30wt%, preferably 5-20wt%.
3. The material according to claim 2, wherein The biological filler is selected from inorganic bioactive materials for bone repair, preferably one or more selected from silicate bioglass, phosphate bioglass, borate bioglass, and hydroxyapatite; The growth factor is selected from one or more of IGF-like insulin growth factor, BMP bone morphogenetic protein, transforming growth factor-β; and / or The antimicrobial agent is selected from broad-spectrum antibiotics and / or non-antibiotic antimicrobial agents; Preferably, the broad-spectrum antibiotic is selected from one or more of vancomycin, gentamicin, cephalosporin, amoxicillin and tobramycin; Preferably, the non-antibiotic antibacterial agent is chlorhexidine.
4. The material according to claim 2 or 3, wherein The biological filler is in the form of particles or fibers; Preferably, The particle diameter of the particle form is 0.5-200 μm, preferably 10-100 μm; and / or The fiber morphology is short fiber morphology, the distribution form is disordered distribution, the fiber length is 0.1-5mm, preferably 0.5-3mm; the fiber diameter is 1-20μm, preferably 3-10μm.
5. A method for constructing the material according to any one of claims 1 to 4, characterized in that: The method includes: (1) forming a precursor solution of a biofunctional filler-hydrogel composite coating; (2) immersing the substrate in the precursor solution, pulling, cyclically freezing-thawing, and salting out; Wherein, the impregnation solution used for salting out is selected from aqueous solutions of sodium salt and / or potassium salt.
6. The construction method according to claim 5, wherein: In step (2), The conditions of the cyclic freezing-thawing include: The freezing temperature is -25 to -15°C; and / or the freezing time is 6 to 24 hours; and / or The thawing temperature is 2-6°C; and / or the thawing time is 6-24h; and / or The number of cycles is 1-6 times, preferably 2-4 times; and / or The conditions of the salting-out treatment include: The impregnation solution is selected from an aqueous solution of one or more of sodium citrate, sodium chloride, sodium sulfate, sodium phosphate, potassium chloride, potassium sulfate, and potassium phosphate; Preferably, the impregnation solution is a mixed aqueous solution of sodium salt and potassium salt, preferably a mixed aqueous solution of sodium citrate and potassium chloride, and the content of sodium citrate and potassium chloride is not less than 40% respectively based on the total molar content of salt in the impregnation solution; and / or The concentration of the impregnation solution is 0.1-3 mol / L, preferably 1-2 mol / L and / or The immersion time is 10-90 min, preferably 10-40 min.
7. The construction method according to claim 5 or 6, wherein: In step (2), The pulling conditions include: The interval time is 10-60 min, preferably 20-30 min; and / or The number of times is 1-10 times, preferably 3-5 times.
8. The construction method according to any one of claims 5 to 7, wherein: In step (1), In the precursor solution of the biofunctional filler-hydrogel composite coating, the content of the biofunctional filler is 1-30wt%, preferably 5-20wt%; and / or The method for forming a precursor solution of a biofunctional filler-hydrogel composite coating comprises: preparing a biofunctional filler, mixing the biofunctional filler with a hydrogel precursor solution; Preferably, the preparation process of the biological functional filler includes: mixing the functional drug with a solvent to obtain a dispersion, spraying it on the surface of the biological filler, and drying it; Preferably, The mass ratio of the functional drug to the solvent is 1:200-2000, preferably 1:500-1500; and / or The solvent is one or more of deionized water, acetic acid, butyl acetate and acetone.
9. The construction method according to any one of claims 5 to 8, wherein: The substrate is subjected to a surface texturing treatment, and the surface texturing treatment includes: performing laser scanning treatment on the surface of the substrate to form a texture; Preferably, the texture is a cross texture or a unidirectional texture, preferably a cross texture.
10. Use of the electrochemical corrosion and degradation resistant material according to any one of claims 1 to 4 in medical implant repair devices.
Citation Information
Patent Citations
Biomedical magnesium alloy surface polydopamine-graphene composite coating and preparation thereof
CN114601962A